DNA Barcoding Reveals Extensive Mislabeling in Seafood Sold in Portuguese Supermarkets. Issue 8 (16th November 2016) - Harris, David James; Rosado, Daniela; Xavier, Raquel
ABSTRACT: Seafood mislabeling is a widespread problem even in Europe where the food market is highly regulated. In the present study, we analyzed the accuracy of seafood labeling in five Portuguese supermarket chains through DNA barcode. Our results show that approximately 19% of examined samples were mislabeled and that the consumer's trust is misplaced. As mislabeling was greater in invertebrate species, we recommend that future studies led by government agencies and scientists aiming to test labeling accuracy should expand from finfish to include invertebrates such as crustaceans and bivalves.